Impact of Building Maintenance Management on Occupant Satisfaction in the ESG Context - Abdulghani, Zaki; Irawan, M. Felik Ferdy; Sukresna, I Made (LifeSciFi, 2025)
Building maintenance management is essential to ensuring the functionality, safety, and comfort of commercial buildings, which directly affects occupant satisfaction. With rapid urbanization and evolving building technologies, the connection between maintenance strategies and user experience is increasingly important, particularly in light of the Environmental, Social, and Governance (ESG) standards for long-term, steady economic expansion. In this study, academic research on the effect of maintenance management on occupant happiness in commercial buildings is identified, assessed, and synthesized using a systematic literature review (SLR). Using a structured methodology including database searches, inclusion criteria, keyword mapping, and quality assessment the review highlights key maintenance dimensions such as responsiveness, cleanliness, safety, facility performance, and environmental sustainability. Findings consistently show that well-managed and proactive maintenance practices significantly improve occupant comfort, productivity, and perceived service quality, while also supporting ESG-related sustainability goals. However, variations in evaluation methods and limited regional data indicate the need for further empirical research. This SLR serves as a foundation for advancing facility management practices and emphasizes the strategic role of ESG integration in achieving long-term occupant satisfaction and sustainable building operations.